ANALISIS PENERAPAN UU-HPP PAJAK PERTAMBAHAN NILAI (PPN) (Study Pada PT.ZEI) - Darmawanto, Darmawanto; Elfiza Abbas, Yeni (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2023)
This research is aimed at understanding whether the implementation of VAT calculations at PT. ZEI is in accordance with HPP Law No.7 of 2021 & has been implemented since April 2022. PT. ZEI chose to be confirmed as PKP because it is part of the private sector which has an obligation to transfer wealth, namely taxes. Data collection methods are through observation studies, interview studies & documentation studies. The data analysis method used is qualitative & quantitative descriptive analysis. The research results show that the implementation, calculation & reporting of VAT is effective and efficient in collecting VAT on Taxable Goods and Services. PT. ZEI can be said to be effective and efficient in collecting VAT on Taxable Goods and Services. The company has printed electronic Tax Invoices, carried out calculations of the Tax Imposition Basis, deposited & reported the Company's Periodic VAT SPT. Implementation of VAT calculation, deposit & reporting carried out by PT. ZEI has complied with applicable tax regulations and has been implemented by the company. As a realization of its tax obligations, PT.ZEI in 2022 (January-March 2022) has recorded output VAT of IDR 275,443,381 and input VAT of IDR 99,398,717 and in April to December 2022) after the harmonization law applied to input VAT amounting to IDR 408,859,093 and output VAT amounting to IDR 647,138,252.